“If your voice isn’t accepted, does it mean you stop talking?” exploring a woman leader’s reversal of postfeminist confidence discourses - Yoong, Melissa (Emerald, 2022)
This study offers a lens for exploring women leaders’ production of resistance through postfeminist discourses. Through the case study of Bozoma Saint John, a high-profile Black C-Suite executive, this study examines micro-acts of subversion and considers the extent they can promote feminist thinking in the corporate world and the implications for feminist theorising about women in leadership. Interviews with Saint John were collected from YouTube and examined using feminist critical discourse analysis informed by intersectionality, feminist poststructuralism and Foucault’s notion of “reverse discourse”. Saint John reproduces elements of the postfeminist confidence discourse to defy stereotypes of Black women, while simultaneously reversing the individualistic conception of confidence in favour of corporate and collective action. This has the potential to facilitate positive change, albeit within the boundaries of the confidence culture. Combining reverse discourse, intersectionality and feminist poststructuralism with a micro-level analysis of women leaders’ language use can help to capture the ways postfeminist concepts are given new subversive meanings. Whereas existing studies have focused on how elite women’s promotion of confidence sustains the status quo, this study shifts the research gaze to the resistance realised through rearticulations of confidence, illustrating how women-in-leadership research can advance feminist theorising without vilifying senior women even as they participate in postfeminist logics of success.